2021
DOI: 10.4049/jimmunol.2100082
|View full text |Cite
|
Sign up to set email alerts
|

CXCR5+CD8+ T Cells: A Review of Their Antibody Regulatory Functions and Clinical Correlations

Abstract: CD8+ T cells have conventionally been studied in relationship to pathogen or tumor clearance. Recent reports have identified novel functions of CXCR5+CD8+ T cells that can home to lymphoid follicles, a key site of Ab production. In this review, we provide an in-depth analysis of conflicting reports regarding the impact of CXCR5+CD8+ T cells on Ab production and examine the data supporting a role for Ab enhancement (B cell helper) and Ab downregulation (Ab-suppressor) by CXCR5+CD8+ T cell subsets. CXCR5+CD8+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
3
8
0
Order By: Relevance
“…This CD8 + T cell subset has been reported to impact biologic outcomes (infection, autoimmunity, malignancy) in various animal models of disease and in humans (reviewed in 46–48 ). Subsets of CXCR5 + CD8 + T cells have been reported to enhance antibody production, 49–58 while others like the antibody‐suppressor CXCR5 + CD8 + T cells in our studies and Qa1‐restricted CXCR5 + CD8 + T cells reported by others inhibit alloantibody 59 and auto‐antibody 60,61 production (reviewed in 62 ). Phenotypic, functional and mechanistic features of the antibody‐suppressor CXCR5 + CD8 + T cells in our studies that distinguish them from other subsets reported in the literature include the absence of PD‐1 expression 23,62 , antigen specific cytotoxic effector function targeting antibody‐producing B cells, 22,23 and regulatory functions that are not associated with FoxP3, IL‐10, ICOS/ICOSL, and CD103 62 …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This CD8 + T cell subset has been reported to impact biologic outcomes (infection, autoimmunity, malignancy) in various animal models of disease and in humans (reviewed in 46–48 ). Subsets of CXCR5 + CD8 + T cells have been reported to enhance antibody production, 49–58 while others like the antibody‐suppressor CXCR5 + CD8 + T cells in our studies and Qa1‐restricted CXCR5 + CD8 + T cells reported by others inhibit alloantibody 59 and auto‐antibody 60,61 production (reviewed in 62 ). Phenotypic, functional and mechanistic features of the antibody‐suppressor CXCR5 + CD8 + T cells in our studies that distinguish them from other subsets reported in the literature include the absence of PD‐1 expression 23,62 , antigen specific cytotoxic effector function targeting antibody‐producing B cells, 22,23 and regulatory functions that are not associated with FoxP3, IL‐10, ICOS/ICOSL, and CD103 62 …”
Section: Discussionsupporting
confidence: 56%
“…Subsets of CXCR5 + CD8 + T cells have been reported to enhance antibody production, [49][50][51][52][53][54][55][56][57][58] while others like the antibody-suppressor CXCR5 + CD8 + T cells in our studies and Qa1-restricted CXCR5 + CD8 + T cells reported by others inhibit alloantibody 59 and auto-antibody 60,61 production (reviewed in 62 ). Phenotypic, functional and mechanistic features of the antibody-suppressor CXCR5 + CD8 + T cells in our studies that distinguish them from other subsets reported in the literature include the absence of PD-1 expression 23,62 , antigen specific cytotoxic effector function targeting antibody-producing B cells, 22,23 and regulatory functions that are not associated with FoxP3, IL-10, ICOS/ ICOSL, and CD103. 62 Our prior work indicates that alloprimed CD8 + T cell-mediated suppression of alloantibody production occurs, in part, by the killing of alloprimed self-IgG1 + B cells (MHC I-restricted alloantigen presentation), which is detected both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…29 Of note, CXCR5expressing CD8 + T cells important for the control of autoantibody generation in the germinal center and for shaping the antibody response to viral infections. [62][63][64] It is important to note that while studies have shown chemokine receptors to be a useful alternative to cytokine detection, proper validation should be carried out to verify findings. This is especially important in disease cohorts, where alterations to chemokine receptor expression may occur in vivo.…”
Section: Characterization Of the Antigen-specific T-cell Responsementioning
confidence: 99%
“…In addition, it is possible to identify circulating Tfh (cTfh) based on CXCR5 and PD‐1 expression 29 . Of note, CXCR5‐expressing CD8 + T cells important for the control of autoantibody generation in the germinal center and for shaping the antibody response to viral infections 62‐64 …”
Section: Introductionmentioning
confidence: 99%